E-PROMOSI SEKOLAH DALAM BENTUK MOTION GRAPHIC - Sembiring, Evaliata Br; Yusera, Genta Victory (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2021)
The Covid-19 pandemic has led everyone to use technology in various interests. The role of technology is very high to help the community, ranging from information sharing, job monitoring, even as a medium of introduction and promotion of a product and service. One of the very high use of technology as digital promotional media is educational institutions. Mondial School has been using only a few promotional media, namely print media such as brochures, banners, and billboards. These media can actually be shared online, but only in the form of still images and only a little information can be conveyed. Therefore, new innovations are needed to promote this school through a full profile. The new innovation in question is a motion graphics product in video format. Motion graphics method using Villamil-Molina approach was then used to analyze the manufacturing process based on Spatial, Temporal, Live Action and Typographic aspects. As for knowing the feasibility of e-promotion, further analysis will be carried out on aspects of motion graphics and respondent perception. This study on respondent perception uses measurement method based on EPIC Model.